Biosynteza beta-karotenui karotenoidów z udziałem drożdży Rhodotorula spp. – przegląd badań - Bogacz-Radomska, Ludmiła; Harasym, Joanna (Biosynthesis of beta-carotene and carotenoids by yeast of Rhodotorulaspp. – a review 9, 2017)
Biosynthesis of carotenoids, including β-carotene, is an area of continuous scientific research due to their valuable pro-health properties and high coloring power. This paper presents an overview of the Rhodotorula spp. culture, esp. methods and conditions applied in carotenoids’ production. In this paper the influence of combined cultures, pH, temperature, carbon sources, the proportion of carbon atoms to nitrogen, concentrations of micro- and macronutrient sources, oxidative stress, UV and VIS radiation as well as culturing methods for carotenogenesis in yeast cells of Rhodotorula spp. was characterized. The list of yeast species from the genus Rhodotorula, which naturally synthesize carotenoids, was presented
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2017, Nr 4 (27), s. 9-22
Keywords: carotenoids; Rhodotorula spp; arotenoidy; β-carotene